Embodying Teaching: A Body Pedagogic Study of a Teacher’s Movement Rhythm in the ‘Sloyd’ Classroom - Andersson, Joacim; Risberg, Jonas (Interchange, 2018)
The article draws on body pedagogics and considers that teaching and learning experiences and outcomes are directly related to the different characteristics of movement behaviour. In this article movement behaviour specifically centres on a sloyd (handicraft education) teacher’s walk through the classroom. The analysis illuminate the specific teaching use of the body as a spatial, temporal and situational movement rhythm in the classroom and how teachers and pupils tune into educational discourses by means of different body techniques. A wireless GoPro camera was attached to the teacher’s chest in order to gain detailed view of pupil–teacher–body–material–tool encounters and a specific visual perspective of the sloyd teacher’s walk. During a 2.5 years fieldwork, 25 wood–metal sloyd lessons were observed and recorded (circa 50 h of video). The study is informed by Dewey’s embodied theory of learning and focus the alternation between active and passive phases in the stream of experience. From such Deweyan perspective the rhythm of an activity for organising experience, is fundamental to the creation of intelligent moving habits. The results show the body pedagogic experiences, outcomes and means by highlighting the teacher’s (a) spatial path by describing mutual relationships between the material arrangement of the classroom, the teacher’s bodily movements and the pupils’ participation in the lesson, (b) temporal pace by his ‘flights and perchings’ through the lessons and how he moves from pupil to pupil and assignment to assignment, (c) specific pacts by describing body techniques and situated teacher–pupil encounters that terminate in an agreement about how to proceed.